Hubungan Sikap Dan Lama Duduk Dengan Keluhan Nyeri Punggung Bawah Pada Siswa SMAN 1 Martapura - Raisa Alya Fayaza (Jurnal Skala Kesehatan, 2025)
Low back pain (LBP) is a common condition among high school students as a result of lazy sitting and non-ergonomic posture. The purpose of this study was to understand the relationship between sitting posture and sitting duration with NPB in students of SMAN 1 Martapura. Using a quantitative correlational analysis design, data were collected through questionnaires assessing sitting posture, sitting duration, pain symptoms, physical activity, and trauma. The results showed a significant relationship between gender (p=0.041), trauma (p=0.001), physical activity (p=0.045), and pain frequency (p=0.000) with NPB. However, there was no significant relationship between body weight, BMI, sitting duration, and sitting posture. The majority of students experienced mild to moderate pain, predominantly female, with irregular physical activity. This study emphasizes the importance of an active lifestyle and ergonomics education from school age to prevent NPD.